Massive digestive bleeding in a 10-year-old boy: surgical treatment - Anavitarte, Eduardo; Arruti, César; Torres, Davir; Bazzano, Héctor (Cirugía del Uruguay, 1972)
A case of acute severe digestive bleeding in a 10 years old boy is reported. It was produced by a peptic yuxtapiloric ulcer and the radical traitment consisted in subtotal gastrectomy. The evolution was satisfactory one year latter.